Emotional Categorization of the International Affective Picture System in a Colombian Sample (2019)
The International Affective Picture System (IAPS) is a battery of images used to induce discrete emotional reactions. In this study an IAPS subsample of 200 images was analysed to elicit discrete negative emotions and propose a new categorization of them, according to which discrete negative emotions (disgust, fear, sadness, or anger) they induce, in contrast to a dimensional model of emotion including emotional valence, intensity, and dominance, usually used in the literature. Through a sample by convenience, 447 participants of 3 universities in Bogotá, Colombia, were recruited and shown 60 IAPS images and asked them to what extent they felt fear, sadness, disgust, anger, happiness, or satisfaction when looking at each image. By using the overlap of 95% confidence intervals of the mean of 6 emotions ratings for every image, results revealed that 51.5% of images induced simple emotions (19.5% fear, 16.5% sadness, 13.0% disgust and 2.5% anger), 43% of images induced complex emotions, including more than one negative emotion, 1.5% emotions mixed one negative and one positive emotion, and 4% were undetermined emotions.